Relationship of transitional regulatory B and regulatory T cells and immunosuppressive drug doses in stable renal transplant recipients - Eman H Ibrahim; Mostafa Aly; Christian Morath; Douaa M Sayed; Naruemol Ekpoom; Gerhard Opelz; Caner Süsal; Volker Daniel (Immunity, Inflammation and Disease, 2021)
Abstract Objectives Regulatory B cells (Bregs) and T cells (Tregs) are thought to be involved in the regulation of graft acceptance in renal transplant recipients. However, mechanisms that affect Breg differentiation and interaction with Tregs are rather unclear. Methods Using eight‐color‐fluorescence flow cytometry, Tregs and CD19+ CD24hiCD38hi Bregs were analyzed in whole blood samples of 80 stable kidney transplant recipients, 20 end‐stage renal disease (ESRD) patients and 32 healthy controls (HC). In addition, differentiation of Bregs and Tregs was studied in different micromilieus using cocultures with strongly enriched B‐lymphocytes and autologous peripheral blood mononuclear cells stimulated with CpG and phytohemagglutinin. Results Bregs were higher in HC than in ESRD patients and lowest in transplant recipients. Bregs were higher early as compared to late posttransplant. Posttransplant, high Bregs were associated with higher glomerular filtration rate (GFR) and lower C‐reactive protein (CRP). Higher doses and blood levels of ciclosporine, tacrolimus, and mycophenolate mofetil as well as higher doses of steroids were not associated with low Bregs. In contrast, most Treg subsets were lower when blood levels of ciclosporine, tacrolimus, and mycophenolate mofetil were higher. Tregs were not associated with Bregs, GFR, CRP plasma levels, and occurrence of rejection or infection. In vitro, differentiation of Bregs was strongly dependent on T cell support and was blocked by excessive or lacking T‐cell help. Tregs were not associated with Breg numbers in vitro. Conclusion Bregs appear to be insensitive to high doses of posttransplant immunosuppressive drugs. The protracted Breg decrease posttransplant might be caused by impaired T cell support attributable to immunosuppressive drugs.